PELATIHAN CHART OF ACCOUNT DI SMA NEGERI 2 JAKARTA - Rennath, Marcella Audrey; Adang, Ferry (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Training on the Chart of Accounts at SMA Negeri 2 Jakarta, focusing on analyzing financial literacy issues. Understanding the chart of accounts is a crucial foundation for students' financial literacy. The need for understanding the chart of accounts is often insufficient in various public schools, including SMA Negeri 2 Jakarta. The activity focused on grasping the fundamental concepts, including definitions, structures, and applying the chart of accounts in the financial education. The results of this phase assisted students in preparing financial information integrated into the chart of accounts to compile accurate financial statements. Financial literacy analysis was conducted at SMA Negeri 2 Jakarta, concentrating on students' awareness of the chart of accounts in managing personal and organizational finances. The findings revealed that understanding the chart of accounts positively contributed to students' financial literacy. This activity involved mentoring in understanding the chart of accounts. Positive results indicated promising progress, with the hope students' financial literacy at SMA Negeri 2 Jakarta could be significantly enhanced. This research provides a concrete overview of the implementation of chart of accounts training at the secondary education level, offering insights into the context of financial education and the role of the chart of accounts in improving students' financial literacy. The activity is successful based on the positive responses from students’ evaluations at the end of the sessions. The implications of the activity include the development of accounting skills by students, increased value for the school as a partner, and marketing benefits for Tarumanagara University.